Claude Cahun, Freudo-Marxism, and Poetry’s Political Action - Frost, Jackqueline (The Nordic Journal of Aesthetics, 2025)
This article examines Claude Cahun’s 1934 pamphlet, Les Paris sont ouverts, conceived as a report to the literary section of the PCF-led Association des écrivains et artistes révolutionnaires (AEAR). I address how Cahun’s intervention generates a set of politico-aesthetic arguments for the place of avantgarde poetics in the context of communist literary culture. These arguments are constructed using what I discuss as surrealism’s form of “aggregate Freudo-Marxism.” Cahun sought to advance the surrealist position within the AEAR and promote avant-garde techniques in poetry as politically efficacious. To illuminate her thought, I analyze surrealism’s relationship to Freudo-Marxism and to Socialist Realism of that period. I then explore Tristan Tzara’s influence on Cahun and the similarity between Cahun’s and Herbert Marcuse’s deployments of Freudian concepts. Finally, I ask how we might contemplate the creation of political ethics, integral to the surrealist project of militancy, today. In this way, Cahun’s conception of poetry’s political action can also be extended to practices beyond the page. The purpose of this article is not to explore Cahun’s communist activism per se, but to elucidate her defense of surrealist Freudo-Marxism and its proposed relationship between poetry and politics, as one response to the question of what historically constitutes a Marxist poetics.